ANALISIS FENOMENA GOLONGAN PUTIH PADA PEMILIHAN GUBERNUR JAWA TENGAH 2013 - Nuri Mukti Yuda Wibawa; Hermini S; Susilo Utomo (Journal of Politic and Government Studies, 2014)
The phenomenon of swing voters in every election in Indonesia is quite interesting to study. Central Java is one of the provinces with a high non-vote behavior rate. Pati District, in Wonogiri District, Temanggung District a county with a high level of non-vote behaviour, moderate, and low in Central Java Province. non-vote behaviour can be regarded as a form of democratic failure. non-vote behaviour when linked with the "right to choose" is the right of every individual to choose or not choose. Each individual is free to choose the party or candidate that coveted and also free to choose any party or candidate.The data used in this study is the type of quantitative data, ie data in the form of numbers or numbers. In accordance with its shape, quantitative data can be processed or analyzed using statistical calculations. According to the logic of the study, this research can be classified as deductive research as a structure of concepts or theories developed for later tested by an empirical observation. Thus this study will describe the facts and explain the circumstances of the research object, based on facts that exist to try to analyze based on the data obtained were correct.These results explain the reason for the cause of responden not interested in voting in the election of the Governor of Central Java, among others, have other activities while governor election, deliberately did not come because I was lazy, and did not get an allowance. Whether or not the governor's race, state of Central Java community will remain the same with empty promises. Likewise also from the standpoint of leadership, Central Java Governor election will be deemed not produce visionary leadership and has an impact on community change Central Java